2017
DOI: 10.1017/s0950268817001820
|View full text |Cite
|
Sign up to set email alerts
|

Association between meteorological factors and reported cases of hand, foot, and mouth disease from 2000 to 2015 in Japan

Abstract: The purpose of this study was to clarify the association between hand, foot, and mouth disease (HFMD) epidemics and meteorological conditions. We used HFMD surveillance data of all 47 prefectures in Japan from January 2000 to December 2015. Spectral analysis was performed using the maximum entropy method (MEM) for temperature-, relative humidity-, and total rainfall-dependent incidence data. Using MEM-estimated periods, long-term oscillatory trends were calculated using the least squares fitting (LSF) method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 31 publications
0
40
1
Order By: Relevance
“…It is well known that weather plays a vital role in the transmission of many infectious diseases (Xiao et al 2017). The seasonality of the incidence of HFMD has led to extensive research by epidemiologists in an attempt to quantify the association with meteorological variables (Huang et al 2018;Sumi et al 2017;Yu et al 2019;Zhao et al 2017). The results obtained from different regions on the effects of various meteorological factors were not entirely consistent, and the temperature-HFMD relationship was the most controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that weather plays a vital role in the transmission of many infectious diseases (Xiao et al 2017). The seasonality of the incidence of HFMD has led to extensive research by epidemiologists in an attempt to quantify the association with meteorological variables (Huang et al 2018;Sumi et al 2017;Yu et al 2019;Zhao et al 2017). The results obtained from different regions on the effects of various meteorological factors were not entirely consistent, and the temperature-HFMD relationship was the most controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown that the association between the incidence of HFMD and seasons or temperatures varied with different regions. Some areas have the peak once a year, such as in summer in Japan [10,11], and in autumn in Finland [12]. Two peaks may occur in other regions, such as in summer and autumn in the United Kingdom [13,14] and Belgium [15].…”
Section: Introductionmentioning
confidence: 99%
“…A temperature of 18°C was associated with the maximum number of HFMD cases, which is consistent with the findings of the multi-city studies conducted in mainland China and Japan. [ 8 , 9 ] Previous studies have suggested that a possible temperature threshold causes the outbreak of HFMD, which may be related to the mechanism of HFMD transmission. By contrast, the thermal effect played an important role in the infectivity of enterovirus.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an inverse V-shaped relationship between the reported number of HFMD cases and temperature was observed in Japan and mainland China. [ 8 , 9 ] While in Wuhan, China, the association between temperature and HFMD incidence showed an approximate “M” shape. [ 10 ] The results of the abovementioned studies were not consistent, which may be due to the significant spatial heterogeneity in the effects of temperature on HFMD incidence.…”
Section: Introductionmentioning
confidence: 99%